Aberrant Expressions of EDNRB and EDN3 in a Multifactorial Hirschsprung Disease - Gunadi; Vujira, Khanza Adzkia; Amadeus, Verrell Christopher; Gabriela, Gita Christy; Amaragati, Adisrasti Rejeki; Geometri, Esensi Tarian; Eryvinka, Laudria Stella; Ferdinandus, Kevin Eliezer; Pramono, Nabila Ardia; Dwihantoro, Andi (Current Pediatric Reviews, 2025)
<span class=
Keywords: development of enteric nervous systems